Partnerská a pedagogická láska: q-metodologická štúdia reprezentácií lásky medzi vysokoškolskými študentami predprimárneho vzdelávania - Ivan Lukšík; Nela Kováčová (Orbis Scholae)
Love, as both an individual experience and a cultural construct, presents unique challenges in educational contexts. This study employs q-methodology to examine how undergraduate students in pre-primary education conceptualize love, drawing on a diverse range of meanings available to them. Our primary questions focus on the origins of these love representations and the role that pedagogical love occupies within them. The study involved 32 students (31 male and one female), who sorted 60 statements about love based on their level of agreement or disagreement. Through q-analysis, three distinct factors emerged: Compounded love, encompassing romantic, spiritual, and primary forms of love; Christian-based love, grounded in Christian values; Strong, mutual love, incorporating elements of mutual affection and potential infatuation. Notably, the third factor also demonstrated the capacity to encompass many aspects of pedagogical love. These findings are discussed within the frameworks of social representations theory and pedagogical love conceptualizations.